Peningkatan Kemampuan Berpikir Kritis : Ditinjau Dari Pengembangan Modul Literasi Dasar Berbasis Alur Merdeka Dengan Bantuan Qr Code - Wulandari, Heni; Padlurrahman, Padlurrahman; Haritani, Hartini (Educatio, 2025)
The teaching module is one of the keys to students' success in achieving learning objectives. In 21st-century learning, students are positioned as the center of the learning process, with the teacher acting as a facilitator. Additionally, a teaching model that aligns with the learning materials can enhance students' critical thinking skills. This study is a development research using the 4D model, which consists of four stages: Define, Design, Development, and Disseminate. The purpose of this study is to develop a basic literacy module based on the Alur Merdeka (Freedom Pathway) approach with QR code assistance to improve students' critical thinking abilities. Based on the validation results by experts, the developed basic literacy module is valid and feasible to be used as a teaching module for the Integrated Science and Social Studies (IPAS) subject. The average material validation score was 74, categorized as “Good,” which falls within the range of 61.2 < X ≤ 75.6. The design/technology validation score was 61, categorized as “Very Good,” within the range of X > 54.67, and the language expert validation score was 55, also categorized as “Very Good,” within the range of X > 49.4. Meanwhile, the responses from teachers and students regarding the practicality of the teaching module showed scores of 100% and 92%, respectively, falling within the “Very Good” category. The trial results, using critical thinking indicators to test the effectiveness of the basic literacy module, showed that it significantly improved students' critical thinking skills, with scores ranging from 84% to 92%, categorized as “Very Good.” Furthermore, the n-gain result reached 0.83, indicating a high category, as it falls within the range of 0.70 ≤ 0.83 ≤ 1.00